Justice and charity : an introduction to Aquinas's moral, economic, and political thought - Krom, Michael P. (Grand Rapids Baker Academic, 2020)
"Introduces Christians to the thought of St. Thomas Aquinas, equipping them to apply their faith to the complex moral, economic, and political problems of contemporary society"--
Includes bibliographical references (pages 227-235) and index.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.